Effect of resistance exercise with arm sleeve compression garments accelerates blood lactate removal: Arm Sleeve Compression Garments Accelerates Blood Lactate Removal - Chiappa, Gaspar Rogerio da Silva (Manual Therapy, Posturology & Rehabilitation Journal, 2021)
Purpose: It has long been suggested that arm sleeve compression garments (CG) may impact blood lactate levels ([Lac-]B) during the recovery from resistive exercise. In this study, we tested the hypothesis that upper-body compression garments during recovery from intense resistive exercise contribute to La clearance, thus leading to reduced [Lac-]B. Methods: Sixteen healthy men underwent two sequences of flexion and extension exercises of the elbows and triceps on a pulley, with and without upper-body compression garments, separated by 72h. The exercises were performed with 3 sets of 10 RM, and a cadence of 2 sec was maintained in the eccentric phase and concentric phase. During an inactive recovery period of 20 minutes, serial arterialized venous blood samples were collected to obtain lactate concentrations. Results: Subjects showed similar responses at baseline and at peak exercise during the two experimental conditions. [Lac-]B during recovery was reduced with the use of upper-body compression garments at 5, 10, 15, and 20 min of recovery (P<0.05). Conclusion: These data are consistent with the notion that compression garments can accelerate lactate removal during recovery from intense exercise.